Abdominal Wall Desmoid during Pregnancy: Diagnostic Challenges. (3rd January 2012) - Awwad, Johnny; Hammoud, Nadine; Farra, Chantal; Fares, Farah; Abi Saad, George; Ghazeeri, Ghina
Abstract : Background . Desmoids are benign tumors, with local invasive features and no metastatic potential, which have rarely been described to be pregnancy associated. Case . We described the rapid growth of an anterior abdominal wall mass in a 40-year-old pregnant woman. Due to its close proximity to the enlarged uterus, it was misdiagnosed to be a uterine leiomyoma by ultrasound examination. Final tissue diagnosis and radical resection were done at the time of abdominal delivery. Conclusion . Due to the diagnostic limitations of imaging techniques, desmoids should always be considered when the following manifestations are observed in combination: progressive growth of a solitary abdominal wall mass during pregnancy and well-delineated smooth tumor margins demonstrated by imaging techniques. This case emphasizes the importance of entertaining uncommon medical conditions in the differential diagnosis of seemingly common clinical manifestations.